2022
DOI: 10.3390/atmos13091515
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Odor-Causing VOCs from the Painting Process of the Automobile Manufacturing Industry and Its Sustainable Management

Abstract: Automotive manufacturing is one of the potential sources of air pollution particularly involving volatile organic compounds (VOCs). This study intensively evaluated VOC emissions and their dispersion from the industry. The measured VOCs were speciated for further evaluation of their odor threats according to the characteristics of each compound. Mathematical emission and air dispersion models were applied to assist in elaborating the source–receptor relationship allowing the determining of existing business-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The simulation results can help policymakers to identify the areas of maximum concentration [61]. For example, Kultan et al (2022) utilized the AERMOD model to predict the odor of industrial VOCs from automobile manufacturing. The key contributor to the smell and appropriate measures in managing industrial air pollution were identified [62].…”
Section: Mathematical Dispersion Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results can help policymakers to identify the areas of maximum concentration [61]. For example, Kultan et al (2022) utilized the AERMOD model to predict the odor of industrial VOCs from automobile manufacturing. The key contributor to the smell and appropriate measures in managing industrial air pollution were identified [62].…”
Section: Mathematical Dispersion Modelingmentioning
confidence: 99%
“…These emissions could be reduced by enclosing the sump in a closed system. Based on previous research, covering the basin dramatically decreased VOC concentrations [62,76,77]. On the other hand, storage tanks also comprised a large proportion of the contributors to BTX concentration; therefore, reducing the ambient concentration should be considered.…”
Section: Percentage Of Contribution Of Btx At Different Receptor Sitesmentioning
confidence: 99%
“…Notably, the odor thresholds of pentanal and hexanal are as low as 0.41 and 0.28 ppb, respectively. The odor of pentanal is characterized by a strongly pungent and ethereal smell, which is particularly unbearable (Nagata, 2003;Kultan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With growing concerns about emissions from solvents and residual volatiles from coatings 37–39 and the fact that UV curing is gaining prominence in additive manufacturing, 40–42 the process reported here holds much promise across a wide range of applications. The polymer–metal oxide hybrid films prepared here can be extended to prepare corrosion-resistant coated substrates, hybrid membranes and functional films using other metal oxides.…”
mentioning
confidence: 99%